Salidroside reduces tau hyperphosphorylation via up-regulating GSK-3β phosphorylation in a tau transgenic Drosophila model of Alzheimer's disease. Issue 1 (December 2016) - Zhang, Bei; Li, Qiongqiong; Chu, Xingkun; Sun, Suya; Chen, Shengdi
Abstract Background Alzheimer's disease (AD) is an age-related and progressive neurodegenerative disease that causes substantial public health care burdens. Intensive efforts have been made to find effective and safe treatment against AD. Salidroside (Sal) is the main effective component ofRhodiola rosea L., which has several pharmacological activities. The objective of this study was to investigate the efficacy of Sal in the treatment of AD transgenicDrosophila and the associated mechanisms. Methods We used tau transgenicDrosophila line (TAU) in which tau protein is expressed in the central nervous system and eyes by the Gal4/UAS system. After feeding flies with Sal, the lifespan and locomotor activity were recorded. We further examined the appearance of vacuoles in the mushroom body using immunohistochemistry, and detected the levels of total glycogen synthase kinase 3β (t-GSK-3β), phosphorylated GSK-3β (p-GSK-3β), t-tau and p-tau in the brain by western blot analysis. Results Our results showed that the longevity was improved in salidroside-fedDrosophila groups as well as the locomotor activity. We also observed less vacuoles in the mushroom body, upregulated level of p-GSK-3β and downregulated p-tau following Sal treatment. Conclusion Our data presented the evidence that Sal was capable of reducing the neurodegeneration in tau transgenicDrosophila and inhibiting neuronal loss. The neuroprotective effects of Sal were associated with its up-regulation of the p-GSK-3β and down-regulation of the p-tau.